Integrasi Nilai –Nilai Karakter Pada Pembelajaran Pendidikan Agama Islam (PAI) Studi di Madrasah Tsanawiyah (MTs) Swasta Kabupaten Kulon Progo Yogyakarta - Salim, Ahmad (Literasi: Jurnal Ilmu Pendidikan, 2015)
Abstract The great consciousness to the character internalization of students through education begins from the government’s concern to the students who have been doing the decency value for example dishonest, no discipline, no respect for teachers, truancy, late which is often done by school students. This research was conducted to reveal the character of students trough the integration character value on PAI learning that held in MTs Maarif Jangkaran, MTs Maarif Wates, MTs Muhammadiyah Wates and MTs Muhammadiyah Sentolo. The method used is descriptive qualitative analysis, with data collection done by observation complemented by interviews and documentation. The results showed that all private MTs at Kulon Progo district integrate the character (religious, honest, independent, communicative, responsible and democratic) in the PAI study done by a particular emphasis on offensive material value problem. In general, the integration of /characters in PAI learning to be effective, because it is supported by the enough facilities at the four private MTs, although there are obstacles integrating character values such as the perception of teachers PAI equalize the character with morals. Keywords: the character, PAI learning